EFEKTIVITAS METODE PEMBELAJARAN EXPERIENTIAL LEARNING DALAM MENINGKATKAN KOMPETENSI KARYA PUISI SISWA KELAS XI SMA SA’ADHATUR DHARAIN KECAMATAN KEDUNGDUNG KABUPATEN SAMPANG - Moh Ari Wibowo; Ernawati; Tatik Maryana (Jurnal Cendekia Pendidikan, 2024)
Learning of writing poetry will naturally lead students to find new ideas or ideas through the emotional experience they have secured during the learning process. problem at senior high school. Sa’adhatur dharain kec. Kedung-dung kab. Sampang related to making literary works, especially poetry. This type of study is research into classroom actions (classroom action reseach). Research is carried out in the classroom context that aims to improve learning practices in class so that they can improve students’ learning process skills and learning outcomes. Based on date obtained during the implementation of class action research in grade XI high school student sa’adhatur dharain kec. Kedung-dung kab. Sampang is known that the effectiveness of the experiential learning method improves the ability to write poetry. That increase can be seen from the changing average class value of the I cycle to II which is 6,4. In the I cycle, the average value a student gets by 70,0 in the category is enough. Meanwhile, in cycle II the average value earned by students is 76,4 in the category both. The response from students after being seen from the results of the questionnaire given to students from 40 students 39 or 97.5 %stated that they were happy, 1 student or 2.5% stated that they were not happy, and 0% expressed dislikes the use of experiential learning methods in writing poetry.